The Merrie Tales of Jacques Tournebroche - France, Anatole, 1844-1924; Allinson, A. R. (Alfred Richard), 1852-1929 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Merrie Tales of Jacques Tournebroche" by Anatole France is a collection of stories likely written in the early 20th century. This work weaves fantastical elements from medieval legends, particularly focusing on characters like Charlemagne and his knights, exploring themes of humor, folly, and morality amidst historical backdrops. The tales blend whimsy and satire, presenting not only heroic deeds but also the absurdities of human nature. At the start of the collection, the characters gather in the grand chamber of King Hugo, indulging in excessive boasting about their martial prowess and feats of strength. Charlemagne and his twelve knights engage in a friendly contest of bravado, making outlandish wagers that highlight their chivalric heritage. However, their merriment is interrupted by the furious King Hugo, who warns them that failure to fulfill their boasts will lead to dire consequences. This opening sets the stage for a blend of adventure and humor, showcasing the knights$1 (Bantics while hinting at deeper reflections on honor and the consequences of one$1 (Bs words. (This is an automatically generated summary.)s
Release date is 2008-05-09
Produced by David Widger
Keywords: France -- Social life and customs -- Fiction; French fiction -- Translations into English